Follicular Conjunctivitis due to Chlamydia felis—Case Report, Review of the Literature and Improved Molecular Diagnostics - Wons, Juliana; Meiller, Ralph; Bergua, Antonio; Bogdan, Christian; Geißdörfer, Walter (Frontiers in Medicine, 2017)
A 29-year-old woman presented with unilateral, chronic follicular conjunctivitis since 6 weeks. While the conjunctival swab taken from the patient´s eye was negative in a Chlamydia (C.) trachomatis-specific PCR, C. felis was identified as etiological agent using a pan-Chlamydia TaqMan-PCR followed by sequence analysis. A pet kitten of the patient was found to be the source of infection, as its conjunctival and pharyngeal swabs were also positive for C. felis. The patient was successfully treated with systemic doxycycline. This report, which presents one of the few documented cases of human C. felis infection, illustrates that standard PCR tests are designed to detect the most frequently seen species of a bacterial genus, but might fail to be reactive with less common species. We developed a modified pan-Chlamydia/C. felis duplex TaqMan PCR assay that detects C. felis without the need of subsequent sequencing. The role of chlamydiae-specific serum antibody titers for the diagnosis of follicular conjunctivitis is discussed.